Mechanical properties and cytotoxicity studies of calcia stabilized zirconia (Ca-SZ) for dental application - Johari, Anis Syamimi (2024)
Several studies can be found on zirconia as dental application but only few of them use calcium oxide (CaO) as its stabilizer. Mechanical aspects and cell studies were not covered, leaving a gap in the evidence regarding the mechanical properties and biocompatibility of Ca-SZ as dental materials. CaO synthesis from calcium nitrate tetrahydrate was used as metal precursor to produce Ca-SZ. Bioceramic Ca-SZ was sintered at three different sintering temperatures 1200°, 1300° and 1400°C. Ca-SZ was characterized using Scanning Electron Microscopy (SEM), Energy Dispersive X-ray Spectroscopy (EDX) element analysis, X-ray Diffraction (XRD) for composition studies. Ca-SZ sample shows a good morphology under SEM observation. Increment of sintering temperature enhance the surface morphologies, the phase of Ca-SZ become intensified and transformed from monoclinic to tetragonal ZrO2 and the flexural strength increases. The mechanical properties for Ca-SZ at temperature 1400°C displayed a good result that was comparable with commercial CEREC Zirconia. Ca-SZ bioceramic sintered at 1400°C had comparable mechanical strength especially with regard to flexural that reach up to 535.3 MPa while CEREC Zirconia goes up to 683.18 MPa and fracture toughness 4.73 MPa m1/2 as that of CEREC Zirconia 4.91 MPa m1/2 The highest viability of Ca-SZ was at 24 hours incubation that reached 95% comparable with CEREC Zirconia at 97%. The LogIC50 of Ca-SZ at 24 hours incubation was 0.20417 mg/ml and comparable with CEREC Zirconia at 0.1995 mg/ml. The development of Ca-SZ can act as an alternative material for dental applications.